Impact of open innovation in Peruvian food firms - Del Carpio Gallegos, Javier Fernando (2022)
Food firms are an important part of Latin American economies, and they face an increasingly competitive context due to their customers’ demands. For this reason, the main objective of this study is to empirically verify how inbound open innovation and absorptive capacity have a positive influence on technological innovations in Peruvian food firms. A model was designed that shows the relationship between the constructs, and it is based on a sample of 111 food firms that participated in the third national innovation survey of the manufacturing industry and knowledge-intensive service firms carried out in 2018. The present study contributes to the literature in the following two ways: First, it contributes to the research of the food industry, which is an industry representative of low-tech intensity industries that lack research; second, it aims to deepen the knowledge about the positive influence of open innovation and absorptive capacity on food firms’ technological innovation capability. As a result, this study has empirically verified how the implementation of inbound open innovation and absorptive capacity improve the technological innovation capability of Peruvian food firms.